2016
DOI: 10.1159/000448028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dapsone in the Treatment of Pemphigus Vulgaris: A Single-Center Case Study

Abstract: Background: Pemphigus vulgaris (PV) is a chronic autoimmune blistering disease. Most patients require long-term therapy with systemic steroids, and a steroid-sparing agent is usually also utilized. Dapsone is a chemotherapeutic agent with anti-inflammatory properties that is used as a steroid-sparing agent in PV. Objective: The aim of the present study was to evaluate the efficacy of dapsone as an adjuvant therapy in patients with PV. Methods: A retrospective analysis of patients' files was performed. All 26 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
5
2
1
Order By: Relevance
“…24 Other studies have also reported similar associations with hypertension, diabetes and hyperlipidaemia. 5,8,12,15,[25][26] None of the pemphigus patients in our study was reported to have thyroid disorders, contrary to previous reports. 9,15,19,25,26 Two PV patients had prior malignancy of nasopharyngeal cancer and breast ductal carcinoma in situ, respectively.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…24 Other studies have also reported similar associations with hypertension, diabetes and hyperlipidaemia. 5,8,12,15,[25][26] None of the pemphigus patients in our study was reported to have thyroid disorders, contrary to previous reports. 9,15,19,25,26 Two PV patients had prior malignancy of nasopharyngeal cancer and breast ductal carcinoma in situ, respectively.…”
Section: Discussioncontrasting
confidence: 94%
“…5,8,12,15,[25][26] None of the pemphigus patients in our study was reported to have thyroid disorders, contrary to previous reports. 9,15,19,25,26 Two PV patients had prior malignancy of nasopharyngeal cancer and breast ductal carcinoma in situ, respectively. Although previous studies 27 had suggested an association of PV with internal malignancy, no significant association was found in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…And on the other hand, one patient responded completely to dapsone although he/she had no neutrophils infiltration. Furthermore, dapsone was also noted as effective in multiple cases of PV [26][27][28][29][30]. A series of three cases were reported by Piamphongsant et al each having distinct clinical scenarios that all responded to dapsone.…”
Section: Discussionmentioning
confidence: 99%
“…Tables I 8 , 10 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 and II 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 illustrate summarized compilations of the RCTs and RCSs carried out to evaluate the adjuvant therapies used in patients with BP and pemphigus, respectively. The confidence of the data presented in this systematic review is ensured based on clear inclusion and exclusion criteria; the search was comprehensive, in that, appropriate databases were used, and there was neither a language bias (no restriction of inclusion based on language) nor restriction of inclusion based on publication status.…”
Section: Methodsmentioning
confidence: 99%